Mechanical tearing of graphene on an oxidizing metal surface. (17th November 2015) - George, Lijin; Gupta, Aparna; Shaina, P R; Gupta, Nandita Das; Jaiswal, Manu
Abstract: Graphene, the thinnest possible anticorrosion and gas-permeation barrier, is poised to transform the protective coatings industry for a variety of surface applications. In this work, we have studied the structural changes of graphene when the underlying copper surface undergoes oxidation upon heating. Single-layer graphene directly grown on a copper surface by chemical vapour deposition was annealed under ambient atmosphere conditions up to 400 °C. The onset temperature of the surface oxidation of copper is found to be higher for graphene-coated foils. Parallel arrays of graphene nanoripples are a ubiquitous feature of pristine graphene on copper, and we demonstrate that these form crucial sites for the onset of the oxidation of copper, particularly for ∼0.3–0.4 μ m ripple widths. In these regions, the oxidation proceeds along the length of the nanoripples, resulting in the formation of parallel stripes of oxidized copper regions. We demonstrate from temperature-dependent Raman spectroscopy that the primary defect formation process in graphene involves boundary-type defects rather than vacancy or sp 3 -type defects. This observation is consistent with a mechanical tearing process that splits graphene into small polycrystalline domains. The size of these is estimated to be sub-50 nm.